Consumer behavior as an advantage. - Esquivel Aguilar, Lizbeth; Véliz Reyna, Carolina; Rodríguez Chapa, Martin Alejandro; Cortés Sánchez, Ruth Yamilet (UANL. Facultad de Contaduría Publica y Administración, 2014)
Organized new developing company may face challenges to start in a new market environment, where the decision planning would take place. Our goal is to get as much customers as we can, so it’s important to give them what they want with the service they expect, so it’s of great importance to have quality, the customers can trust in the company, the product they offer has quality, so they’ll want to purchase what the company has to offer; but isn’t just about the quality, it’s also about the price, the customers always want the less expensive item, so it’s important to make a balance of how much it cost to produce the product and how much the customer it’s willing to pay, to archive the most convenient cost. That's why we analyzed and structured the best strategies to get our market under control and take advantage of our customer behavior.